Impacts of COVID-19 on Firms in Vietnam, Report No. 2 : Results from the 2nd Round of COVID-19 Business Pulse Survey - Tan, Shawn; Tran, Trang (World Bank, Washington, DC, 2020)
Vietnam reacted early to the spread of COVID-19 by imposing social distancing measures and mobility restrictions. Firms are recovering on average with further reopening and lower revenue loss. Firms also reported lower incidence of reduced hours worked, reduced demand, and input disruptions. However, the extent of sales drop is still extensive (-36% relative to last year) and net employment has not recovered, staying significantly below the January level.